2020
DOI: 10.1111/hepr.13497
|View full text |Cite
|
Sign up to set email alerts
|

Artificial liver treatment improves survival in patients with hepatitis B virus‐related acute‐on‐chronic liver failure: A case‐control matched analysis

Abstract: Aim The artificial liver support system (ALSS) is recognized as a bridge to liver transplantation in hepatitis B virus‐related acute‐on‐chronic liver failure (HBV‐ACLF) patients. However, patient survival remains unknown. We aim to assess the effects of ALSS on survival in HBV‐ACLF patients. Methods The clinical data of HBV‐ACLF patients receiving standard medical treatment (SMT) plus ALSS (ALSS group, n = 507) or only SMT (SMT group, n = 417) were collected for survival assessment. The main end‐points were cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(39 citation statements)
references
References 28 publications
2
35
0
1
Order By: Relevance
“…Therefore, these 2 most effective methods have not been carried out in all patients. [ 18 , 19 ] A growing body of research have shown that TCM enema can improve the clinical efficacy and quality of life of HBV-ACLF patients. Intestinal endotoxemia is the main pathogenesis of hepatocyte necrosis, so that reducing intestinal endotoxemia and avoiding intestinal infection is the key to the treatment of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, these 2 most effective methods have not been carried out in all patients. [ 18 , 19 ] A growing body of research have shown that TCM enema can improve the clinical efficacy and quality of life of HBV-ACLF patients. Intestinal endotoxemia is the main pathogenesis of hepatocyte necrosis, so that reducing intestinal endotoxemia and avoiding intestinal infection is the key to the treatment of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Не дивлячись на досягнення медицини та постійне впровадження нових медичних технологій у практику з метою контролю над інфекційними процесами, вірусні гепатити є суттєвою причиною підвищення захворюваності та смертності [1][2][3][4]. На сьогодні у світі 1 млрд інфікованих та 350 млн чоловік носіїв вірусу ГВ, які є постійним резервуаром та джерелом інфекції [5].…”
Section: вступunclassified
“…Recent advances in nucleoside/nucleotide analogue (NA) therapy have enabled viral suppression, hepatitis B surface antigen reduction, and improvement of treatment adherence in chronic hepatitis B [1][2][3][4][5] leading to reduce the development of hepatocellular carcinoma (HCC) and liver-related death. [6][7][8] However, despite good suppression of hepatitis B virus (HBV) by NA, there are still cases of HCC development. Therefore, identification of high-risk patients of hepatocarcinogenesis is an important clinical issue, even in patients receiving NA treatment, and the utility of HCC prediction models such as REACH-B, PAGE-B and modified PAGE-B (mPAGE-B) has been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Recent advances in nucleoside/nucleotide analogue (NA) therapy have enabled viral suppression, hepatitis B surface antigen reduction, and improvement of treatment adherence in chronic hepatitis B 1–5 leading to reduce the development of hepatocellular carcinoma (HCC) and liver‐related death 6–8 . However, despite good suppression of hepatitis B virus (HBV) by NA, there are still cases of HCC development.…”
Section: Introductionmentioning
confidence: 99%